Phytoplankton community composition links to environmental drivers across a fjord to shelf gradient on the central coast of British Columbia - Del Bel Belluz, Justin; Jackson, Jennifer M.; Kellogg, Colleen T. E.; Peña, M. Angelica; Giesbrecht, Ian J. W.; Hobson, Louis A. (Frontiers in Marine Science, 2024)
This study characterized phytoplankton communities from 2018 to 2020 across a fjord, channel and shelf station transect on the central coast of British Columbia, Canada. Monthly samples were collected for microscopy-based taxonomy and pigment-based phytoplankton composition (i.e. CHEMTAX and size-fractionated chlorophyll). Early spring blooms were observed at the fjord station suggestive of a sheltering effect from winter wind conditions. Later spring blooms were observed at the channel station, which coincided with seasonal wind reductions, increased sunlight and the freshet. Compositionally, phytoplankton communities at all stations clustered into six groups with redundancy analysis highlighting distinct physical-chemical conditions. The first three clusters were flagellate-dominated (mainly cryptophytes) including samples from all stations and displayed positive correlations with nutrients. Two of these clusters represented low biomass winter conditions while the third included moderate biomass spring and autumn blooms. The remaining three clusters were diatom-dominated and spanned much of the growing season. The first diatom cluster was composed of fjord samples from all years and channel and shelf samples from 2020. These samples were dominated by S. marinoi under moderate nutrient and high stratification and freshwater discharge conditions. The second diatom cluster represented spring and summer bloom conditions at all stations and years, showed high diatom diversity (e.g. Skeletonema marinoi, Chaetoceros and Thalassiosira spp.), and was associated with nutrient depletion. Finally, the third diatom cluster was largely observed in the summers of 2018 and 2019 at the shelf station and included harmful Rhizosolenia setigera and Pseudo-nitzschia seriata blooms under high surface water salinity and temperature. These results show high variability in phytoplankton dynamics across relatively short distances and highlight that, in the northeast Pacific, climate-driven changes to freshwater, temperature and wind dynamics could have profound influences on coastal phytoplankton communities and ecosystems.